Area-Preserving Parameterizations for Spherical Ellipses - Guillén Serrano, Ibón; Ureña, Carlos; King, Alan; Fajardo, Marcos; Georgiev, Iliyan; López-Moreno, Jorge; Jarabo, Adrian (Jornada de Jóvenes Investigadores del I3A, 2018)
We present new methods for efficient estimation of the radiance incoming from disk-shaped light sources. For that, we introduce three novel area-preserving mappings for the projected solid angle of the disk. Our methods significantly improve over previous work, and have been implemented in a mainstream production-oriented render engine..